Knowledge, attitude, and behavior (KAB) of adolescents on eating breakfast in selected public and private high schools in Metro Manila (2011)
Studies suggest that eating breakfast has nutrition and health benefits. While studies on eating breakfast among adolescents are limited, these data are important for planning effective programs for this age group. This study determined the knowledge, attitude, and behavior (KAB) and the factors that affect the adolescents' behavior on eating breakfast. This is a cross-sectional study participated in by 658 high school students from two public and private schools in Manila. A pre-tested questionnaire was used to investigate the knowledge, attitude, and breakfast eating habits of the students. Descriptive statistics was used in discussing the knowledge, attitude, and behavior of the students on eating breakfast. Likewise, Chi-square test was used to determine the relationship between knowledge and attitude and breakfast eating habits of adolescents. Around half of the students had medium level knowledge based on test scores. Data showed that about 2/3 of the students were influenced by teachers to eat breakfast. Attitude toward eating breakfast was strongly positive. While almost all of the students took their breakfast, about a third reportedly were skipping breakfast. Not having enough time was the primary factor influencing their decision to skip breakfast. When eating out, students from public ate at the school canteen, while private school students preferred eating at fast food establishments. The percentage of students from public schools who took softdrinks was significantly higher than in private schools. In public schools, more students took breakfast when it was the mother who prepared it. Most common reasons cited by students for taking breakfast were "I feel it is important to eat breakfast" and "I feel better if I eat breakfast". In conclusion, most students showed medium level of knowledge and a positive attitude on having breakfast. The percentage of students who took breakfast was higher compared to those who skipped breakfast. The majority of those who ate their breakfast preferred to have it at home and when it was the mother who prepared it (68.2% public and 65.9% private). Although there was just a small percentage that skipped breakfast, every opportunity by the school to include breakfast meal as a means of improving the nutritional status of children should be explored. Further studies should also investigate the role of peer influence, perceptions, and belief system on the adolescent's eating habits.